Balance exercise in patients with chronic sensory ataxic neuropathy: a pilot study. Issue 2 (June 2014) - Riva, Nilo; Faccendini, Simone; Lopez, Ignazio D.; Fratelli, Annamaria; Velardo, Daniele; Quattrini, Angelo; Gatti, Roberto; Comi, Giancarlo; Comola, Mauro; Fazio, Raffaella
Abstract: Although exercise therapy is considered part of the treatment of neuropathic patients, and somatosensory input is essential for motor learning, performance and neural plasticity, rehabilitation of patients with sensory ataxia has received little attention so far. The aim of this prospective pilot study was to explore the short‐ and medium‐term efficacy of a 3‐week intensive balance and treadmill exercise program in chronic ataxic neuropathy patients; 20 consecutive patients with leg overall disability sum score (ODSS‐leg) ≥2, absent/mild motor signs, clinical and therapeutic stability ≥4 months were enrolled. Evaluations were done at baseline, at the end of treatment and at 3‐ and 6‐month follow‐up. Outcome measurements included: ODSS‐leg, Berg balance scale, 6‐min walk distance, and the functional independence measure (FIM) scale. The short‐form‐36 health status scale (SF‐36) was used to measure health‐related quality of life (HRQoL). ODSS‐leg improved significantly compared with baseline, 3 weeks, 3 months (primary outcome), and 6 months follow‐up. A significant improvement in all functional secondary outcome measurements and in some SF‐36 subscales was also observed. This pilot study suggests that balance exercise is safe and well tolerated and might be effective in ameliorating disability and HRQoL in patients with chronic peripheral sensory ataxia.